Colorimetric parameters of national flags of UKRAINE and BULGARIA - Diakov, D.; Chebotarova, I. (ТОВ «Видавництво Ліра-К», 2025)
The necessity of standardizing the colors of state flags is discussed. The main colors of the Ukrainian and Bulgarian state flags and their numerical parameters in different color reproduction systems are presented. The procedure for controlling color characteristics by the method of comparison with standard samples is described.
Keywords: color; national flags